Keusahawanan berasaskan sunnah Rasulullah S.A.W : kajian pengalaman dalam kalangan usahawan Melayu MARA Kedah - Hazirah, Omar (2017)
The development of entrepreneurship among Malays is increasingly encouraging due to driven by numerous forms of assistance from relevant government agencies such as Majlis Amanah Rakyat (MARA). The development is also said to have been influenced by theories from Max Weber and McClelland, which relate the religious values with and the needs for achievement to entrepreneurial characteristics. However, studies on how Islamic worldview views this commercial activity and the entrepreneurial characteristics of the Prophet Muhammad S.A.W are still lacking. Moreover, entrepreneurial practices based on the sunnah among Malay entrepreneurs is yet to be discovered. Therefore, this study had identified the Islamic worldview pertaining to entrepreneurial activities, elaborated on the entrepreneurial elements that are based on the sunnah of the Prophet S.A.W and analyzed the level of its practices among Malay entrepreneurs. Since the entrepreneurial concept based on the sunnah is a broad concept, this study is focused on three main concepts, which are faith (akidah), sharia (syariah) and morals (akhlak). This study has also involved 268 small and medium entrepreneurs who received funding from MARA that amounted to no more than RM10,000. This quantitative and qualitative research uses a case study approach. The data were obtained through questionnaires and literature review. The findings indicate that the level of entrepreneurial practices based on the sunnah of the Prophet S.A.W among Malay entrepreneurs is high and fast becoming a trend. Hopefully, the results of this study would become an authoritative reference to all parties, especially Malay entrepreneurs and it can help MARA and relevant government agencies in planning more efficient and holistic entrepreneurial development plans. In addition, this initiative should be able to establish an entrepreneurial identity similar to the sunnah of the Prophet S.A.W, not only in the implementation of commercial activities but also in the implementation of social entrepreneurship based on the Islamic worldview.